A Review on Nanocellulose and Its Application in Supercapacitors. Issue 12 (13th October 2021) - Sezali, Nur Atirah Afifah; Ong, Hui Lin; Jullok, Nora; Villagracia, Al Rey; Doong, Ruey‐An
Abstract: Commercially available supercapacitors offer very limited advantages over other energy storage devices. Balancing their electrochemical performance such as capacitance, energy density, and cyclability is challenging. Studies have shown that this challenge can be overcome by using light and cheap substrates that are highly stable with solvents, and have high loading capacities and compatibility with nanomaterials. Nanocellulose, derived from wastes or biomass, is a good candidate for integrating with other nanosize conductive materials, such as carbon, conducting polymers, and metal oxides, as active materials or nanocomposites for supercapacitors. This review focuses on the properties and preparation of nanocellulose sourced from wastes (biomass) and bacteria, and extends to emerging materials, such as metal–organic frameworks and MXene, for nanocellulose‐based supercapacitors. Even though supercapacitors are mainly composed of electrodes, electrolytes, and separators, this paper focuses on the overall electrochemical performance of nanocellulose‐based supercapacitors to evaluate the influence of nanocellulose. In addition, the potentials and possible limitations of nanocellulose in supercapacitors are discussed. Overall, the incorporation of waste‐derived nanocellulose into energy storage applications is an initiative that improves the circular economy and supports environmental sustainability. Abstract : This review includes the properties and production of nanocellulose; cellulose nanofibers, cellulose nanocrystals, and bacterial cellulose. The integration of nanocellulose with other materials such as carbon materials, conducting polymers, metal oxides, metal organic frameworks, and MXene as composites for the application of supercapacitors is discussed. The prospect and limitations of nanocellulose‐based supercapacitors are also covered in this review